Culture of the Microalga Chlorella vulgaris on Different Proportions of Sugar Mill Effluents (Biological Sciences - PJSIR, 2006)
. Chlorella vulgaris was cultured in four different dilutions of sugar mill effluent media (SMEM). Bold’s basal medium (BBM) was used as the control under laboratory conditions. Maximum cell growth and chlorophyll-a content were obtained on 10th day of the culture in 50% diluted SMEM, followed by those grown in BBM, and 75, 25 and 100% SMEM at stationary phase. The specific growth rate (mg/day) of cells and chlorophyll-a of C. vulgaris grown in 50% SMEM varied significantly (p < 0.01) from those of C. vulgaris cultured in BBM, followed by other SMEM concentrations. Total biomass of C. vulgaris, cultured in 50% SMEM, was found to be significantly higher (p< 0.01) than that of C. vulgaris cultured in BBM, and 25, 75 and 100% SMEM concentrations. Similar trend was also observed in the case of optical density. Cell number and chlorophyll-a of C. vulgaris were highly (p < 0.01) and directly correlated with chlorophyll-a (r2 = 0.991) of C. vulgaris and optical density (r2 = 0.989) for the culture media containing C. vulgaris, respectively. Crude proteins and crude lipids of C. vulgaris, grown in 50% SMEM, were significantly (p < 0.01) higher than those of C. vulgaris cultured in other SMEM concentrations. Due to good growth performance exhibited in the 50% SMEM dilution, the sugar mill effluent may be used for efficient cultivation of• vulgaris and possibly other microalgae.